High-throughput sequencing technology facilitates the discovery of novel biomarkers for antiphospholipid syndrome - Liu, Qi; Yang, Shuo; Tan, Yuan; Cui, Liyan (Frontiers in Immunology, 2023)
Antiphospholipid syndrome (APS) is characterized by arterial and venous thrombosis and/or morbid pregnancy, accompanied by persistent antiphospholipid antibody (aPL) positivity. However, due to the complex pathogenesis of APS and the large individual differences in the expression of aPL profiles of patients, the problem of APS diagnosis, prognosis judgment, and risk assessment may not be solved only from the antibody level. It is necessary to use new technologies and multiple dimensions to explore novel APS biomarkers. The application of next-generation sequencing (NGS) technology in diseases with a high incidence of somatic mutations, such as genetic diseases and tumors, has been very mature. Thus, we try to know the research and application progress of APS by NGS technology from genome, transcriptome, epigenome and other aspects. This review will describe the related research of NGS technology in APS and provide more reference for the deep understanding of APS-related screening markers and disease pathogenesis.